Physical activity and respiratory muscle strength in elderly: a systematic review - Fabio Dutra Pereira; Wagner Oliveira Batista; Patrícia dos Santos Claro Fuly; Edmundo de Drummond Alves Junior; Elirez Bezerra da Silva
Introduction The aging will inevitably bring some kind of functional decline in elderly, sarcopenia in this sense stands out because it damages the muscle function and extend also to the respiratory muscles. Objective Systematically review studies that have sought to compare the strength of respiratory muscles between sedentary and physically active elderly in training programs nonspecific respiratory musculature. Materials and methods From the descriptors motor activity, respiratory muscles and elderly, the databases LILACS, MedLine, Cochrane, PEDro, Scirus and Redalyc were consulted. Results Of 1.263 experiments available in said databases, 12 were recovered and 6 were selected due they meet all the inclusion criteria and selection requirements. Conclusion Physical activity programs offered by the selected studies led physically active elderly to have respiratory muscle strength statistically higher than the sedentary. However, this condition did not expressed itself as security to these elderly to present strength levels above of the minimum predictive of normality.